Relationship between the Lean and Agricultural Companies - Nagy, Vivien Ágnes; Kozma, Tímea; Balogh , Antal (International Journal of Engineering and Management Sciences, 2020)
Eliminating losses is a daily challenge for both: companies and individuals in society. Whether through the production or office work, we are wasting the most important human needs: time and energy with useless things and processes. Both are an integral part of our daily lives and are particularly important for agricultural companies. In our study, we look at the relationship between Lean and agricultural companies. We outline the risks associated with these seven Lean Losses at these companies, and how these problems can be corrected and eliminated using current methods. Our research sheds light on how technological innovations affect and influence the position of companies in the market and in financial and human resources. We examine the benefits and drawbacks of the innovations applied and the Lean processes used, and how they affect the environment around them.